2019
DOI: 10.1108/jieb-07-2018-0026
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing satisfaction and revisit intention among international exchange students in Malaysia

Abstract: Purpose Although studies have examined the role of physical factors such as physical environment, price/fee and personal safety in the satisfaction of international students, the effect of social factors such as emotional support, ethical conduct and student–lecturer attachment in international student’s satisfaction has yet to be explored. This study aims to investigate the effect of physical and social factors associated with the satisfaction of international university exchange students that leads to revisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 77 publications
4
32
0
Order By: Relevance
“…It has indicated that tourists' dissatisfaction will result in unfavourable future behavioral intentions (Zeithaml & Bitner, 2000). There have been several studies investigating the intentions to revisit among tourists and the findings are consistent with results from consumer behaviour investigation (Cheliah et al, 2019;Kim & Shim, 2019;Seetanah et al, 2018). The importance of travellers' involvement was highlighted in defining their intents to revisit (Zhang et al, 2018).…”
Section: H3: Perceived Values Are Positively Related To Tourists' Satsupporting
confidence: 67%
“…It has indicated that tourists' dissatisfaction will result in unfavourable future behavioral intentions (Zeithaml & Bitner, 2000). There have been several studies investigating the intentions to revisit among tourists and the findings are consistent with results from consumer behaviour investigation (Cheliah et al, 2019;Kim & Shim, 2019;Seetanah et al, 2018). The importance of travellers' involvement was highlighted in defining their intents to revisit (Zhang et al, 2018).…”
Section: H3: Perceived Values Are Positively Related To Tourists' Satsupporting
confidence: 67%
“…Prior literature on the experience of international students revealed that the overall experience of these students had a positive direct effect on their institutional recommendations (Ammigan and Jones, 2018) and satisfaction (Chelliah et al, 2019). Satisfaction has a positive and significant link with the likelihood of an institutional recommendation or an intention to revisit (Mavondo et al, 2004;Chelliah et al, 2019). The detailed theoretical explanations for the inter-construct relationships depicted in Figure 1 will be further explained in this section.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 91%
“…1995) and is being shaped continually by repeated experiences in campus life (Elliott and Shin, 2002). Prior literature on the experience of international students revealed that the overall experience of these students had a positive direct effect on their institutional recommendations (Ammigan and Jones, 2018) and satisfaction (Chelliah et al, 2019). Satisfaction has a positive and significant link with the likelihood of an institutional recommendation or an intention to revisit (Mavondo et al, 2004;Chelliah et al, 2019).…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples, however, limited to the first-year international students. In a recent study, Chelliah et al (2019), divides the attracting factors into two, which are a physical factor and social factor. Out of the six variables used, only four have positive relationships with international exchange students' satisfaction, which are a student-lecturer attachment, personal safety, price/fee, and physical environment.…”
Section: Introductionmentioning
confidence: 99%